1993
DOI: 10.1016/1044-0305(93)80006-k
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of the true effect of experimental parameters on the reduction / oxidation processes observed in fast-atom bombardment/liquid secondary spectrometry

Abstract: The peak intensities observed in the molecular ion regions of fast-atom bombardment/liquid secondary ion mass spectra contain contributions from the parent ion species, its one- and two-electron reduction/oxidation products, and chemical background signal due to beaminduced damage. There are several solution and instrumental parameters that can affect the distribution of peak intensities in the molecular ion region. In this study, the analyte concentration and primary beam density and energy were varied system… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
3
0

Year Published

1994
1994
2006
2006

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 33 publications
1
3
0
Order By: Relevance
“…The image consisted of a bright central region of fairly uniform intensity, surrounded by a diffuse ring of much lower intensity, as has been observed elsewhere [15]. At the short gun-target distance employed (-4 Emission Current (rnA) Visentini et al [26] observed similar saturation at high flux. The detailed reasons for this saturation are under study.…”
Section: Resultssupporting
confidence: 58%
See 2 more Smart Citations
“…The image consisted of a bright central region of fairly uniform intensity, surrounded by a diffuse ring of much lower intensity, as has been observed elsewhere [15]. At the short gun-target distance employed (-4 Emission Current (rnA) Visentini et al [26] observed similar saturation at high flux. The detailed reasons for this saturation are under study.…”
Section: Resultssupporting
confidence: 58%
“…The beam-induced reduction of methylene blue has been studied extensively [14,[16][17][18][19][20][21][22][23][24][25][26]. For the purposes of this discussion, only the I-hydrogen atom reduction product will be considered, although 2-hydrogen atom reduction can also be extensive.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Therefore, the formation of metallocorrole positive ions in‐source from divalent metal cations could involve the oxidation of the metal centre. Although atom/ion bombardment induced reductions are well known and are widespread reactions, atom/ion bombardment induced oxidation reactions are much less common 28–31. On the other hand, oxidation reactions in the metal capillary sprayers of mass spectrometers operating in the positive mode are an important step in the overall ionization process, being responsible for charge balance 32, 33…”
Section: Introductionmentioning
confidence: 99%